Multi-template imprinted solid-phase microextraction coupled with UPLC-Q-TOF-MS for simultaneous monitoring of ten hepatotoxic pyrrolizidine alkaloids in scented tea - Luo, Zhimin; Chen, Xueqiang; Ma, Yirong; Yang, Fan; He, Na; Yu, Liangwei; Zeng, Aiguo (Frontiers in Chemistry, 2022)
Pyrrolizidine alkaloids (PAs) are a series of ubiquitous natural toxins in flowering plants, which are associated with serious hepatic disease in humans. However, the simultaneously fast and sensitive monitoring of different PAs are still challenge because of the diversity of PAs and huge amount of interference in complex samples, such as scented tea samples. In this study, molecularly imprinted solid phase microextraction (MIP-SPME) fibers were fabricated by using multi-template imprinting technique for selective recognition and efficient enrichment of different PAs from scented teas. MIP-SPME could be used for selective adsorption of ten types of PAs through specific recognition cavity and strong ionic interaction, including senecionine, lycopsamine, retrorsine, heliotrine, lasiocarpine, monocrotaline, echimidine, erucifoline, europine and seneciphylline. The extraction parameters were also optimized including extraction time, elution solvent and elution time. Then, ultra performance liquid chromatography- quadrupole-time of flight mass spectrometry (UPLC-Q-TOF-MS) coupled with MIP-SPME method was developed for fast, simple, sensitive and accurate determination of ten PAs in scented teas. The established method was validated and presented satisfactory accuracy and high precision. It was also successfully applied for simultaneous determination of ten PAs in different scented tea samples. PAs were found in most of these scented tea samples, which suggest the cautious use of scented tea for consumers.